TRANSFORMATION OF FORMS OF DOING BUSINESS FROM TRADITIONAL TO ELECTRONIC THE EXAMPLE OF THE BANKING SECTOR - Ekaterina Butenko; Sabiyat Magomedsaidova (Вестник Северо-Кавказского федерального университета, 2022)
Society at the present stage of development stands on the verge of a new era - the digital society and digital economy. The problem of globalization and acceleration in all spheres of life of society and the economy in particular, bear a systematic character, it is necessary to correctly assess the prospects, benefits and risks associated with it. Banking is a Prime example of the transformation of traditional types of offer electronic financial services. The concept of "mobile app" is regarded not as an addition to the basic services, and as a form of development of the banking sector and an integral part of it.